Sustainable Credit Risk Governance : A Systematic Review of ERM, ESG, and Digital Readiness in MSME Financing in Indonesia - Hari Satriyono (ITB AAS Indonesia Surakarta, 2025)
Micro, Small, and Medium Enterprises (MSMEs) contribute 61.7% to Indonesia’s GDP and absorb 97% of the national workforce, yet more than 70% still lack access to formal financing. The banking sector faces a structural dilemma between financial inclusion objectives and prudent risk management, reflected in rising MSME non-performing loans (NPLs) which reached 4.41% in June 2025, equivalent to Rp 66.3 trillion of distressed credit. This study aims to develop a Sustainable Credit Risk Governance Model by integrating Enterprise Risk Management (ERM), Environmental, Social, and Governance (ESG) principles, and digital readiness in MSME financing. Using a Systematic Literature Review (SLR) approach following PRISMA protocols, this research synthesized 45 peer-reviewed articles published between 2013 and 2025 from Scopus, Web of Science, and Google Scholar. The findings indicate that banks implementing ESG-integrated credit assessments tend to experience lower NPLs and more stable net interest margins, while digital readiness enhances MSME credit access and reduces information asymmetry through alternative data and advanced analytics. This study proposes a four-layer Sustainable Credit Risk Governance Model consisting of : (1) Risk Governance Layer, (2) ESG Assessment Layer, (3) Digital Analytics Layer and (4) Stakeholder Engagement Layer. The integrated framework offers strategic implications for regulators, banks, and policymakers in aligning financial sustainability, risk-based supervision, and inclusive MSME financing in Indonesia.